Reducing electrostatic charge on spacer devices and bronchodilator response - Wildhaber, Johannes H (Blackwell Science Inc, 2000)
AIMS: Plastic spacers are widely used with pressurized metered dose inhalers (pMDI). Reducing electrostatic charge by washing spacers with detergent has been shown to greatly improve in vitro and in vivo drug delivery. We assessed whether this finding is associated with an improved bronchodilator response in adult asthmatics. METHODS: Twenty subjects (age 18–65 years) with a known bronchodilator response inhaled in random order salbutamol from a pMDI (Ventolin®) through an untreated new spacer (Volumatic®) and through a detergent washed spacer. Patients received the following doses of salbutamol via pMDI at 20 min intervals: 100 µg, 100 µg, 200 µg, 400 µg, 800 µg. Spirometry, heart rate and blood pressure were checked prior to each dose and 20 min after the last dose. RESULTS: There were no differences between baseline forced expiratory volume in 1 s (FEV(1)) using either spacer (2.61 ± 0.56 and 2.52 ± 0.45 l, untreated and treated with detergent, respectively; mean ±s.d.). The provocation dose required to cause a clinically significant improvement of 10% in FEV(1) (PD10) was significantly lower when the detergent treated spacer was used (1505 ± 1335 and 430 ± 732 µg, untreated and treated, respectively, P < 0.002). CONCLUSIONS: We have demonstrated an improvement in bronchodilator response, in adult asthmatics, after reducing the electrostatic charge in a spacer device by washing it with ordinary household detergent. This finding stresses the importance of an optimal choice of delivery device for asthma medication.